Methods of Assessing the Economic Impact Investing in the Development of Intellectual Resources - Roman E. MOISEEV; Gaziz F. MINGALEEV; Rafik Z. VALIULLIN; Mansur F. SAFARGALIEV (Communications of International Proceedings, 2020)
In modern times, the process of making a decision on whether to invest in education or not is complicated. When a person decides to invest in education and continuing education, his expectations regarding his future income play a significant role in this matter. Since the results of investment in education appear in the form of higher wages, it is possible to conclude if the investment was profitable and efficient. The main practical problem is associated with the lack of scientific tools which determine the relationship between the competencies formed at the training stage and the results that are obtained by the both sides interested in the development of intellectual resources. Along with the transition to the digital economy, significant changes are taking place in the labor market. The demand for professions that are associated with the performance of repetitive formal operations is decreasing. Instead there is a growing demand for specialists who can deftly use digital technologies for the benefit of business, competence profiles are changing; new professions continue to appear, the requirements for staff flexibility and adaptability are increasing as well as the need to obtain supra-professional skills (“soft skills”). In this regard, the purpose of the article is to create a measuring toolkit for assessing the results of investment in the development of intellectual resources. The proposed toolkit allows for a more accurate setting of educational tracks on the basis of technical specifications of employers' enterprises and allows accelerating the process of paying off the investment in the development of intellectual resources. The authors attempted to describe mathematically the relationship between the competencies formed at the training stage and the results achieved by the participants in the development of intellectual resources. A particular feature of the proposed economic and mathematical tools is the ability to quantitatively measure the relationship between competencies and wages. At the same time, the authors note down that this method is developing in the direction of paying attention to the formation of professional competencies and personal qualities in the development of intellectual resources.
Keywords: Intelligence; Competence; Investment; Resource; Efficiency; Education; Production; Competition; Leadership.